Developing the drilling tool for trenchless pipeline construction; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Povarnitsyn S. (Latest Technologies in Oil and Gas Driling, 2016)
Title screen